Science Learning with The Qur'an and Hadith Through Audiovisual Media (Video) to Improve Concept Mastery and Religious Attitude - Ibni Annas; Irvan Permana; Aini Azizah Ramli (JSEP (Journal of Science Education and Practice), 2022)
This study aims to improve students' concept mastery and religious attitudes in science learning with the Quran and Hadith contents through audiovisual media (video). The research design was quasi-experimental, with experimental and control classes as the research subjects. Data were collected using a test to measure students' concept mastery and religious attitudes with 30 questions, an observation sheet, and a questionnaire with 22 questions. The measurement results of the two test forms were analyzed in N-Gain, while the observation sheets were analyzed descriptively. Students' responses were analyzed in percentage. The results showed that students who learned using the Qur'an and Hadith content through the media were much better than through non-media learning. The N-Gain score for concept mastery was 50.77% (medium) and 38.56% (medium), while for religious attitude was 3.25 (good) and 3.61 (very good). This study proves that the implementation of science learning with the content of the Qur'an and Hadith in teaching and learning activities is quite good, and students' responses to the learning implementation are quite high.